Anti‐PD1‐Induced Immune‐Related Adverse Events and Survival Outcomes in Advanced Melanoma. (12th February 2020) - Suo, Aleksi; Chan, Yin; Beaulieu, Carissa; Kong, Shiying; Cheung, Winson Y.; Monzon, Jose G.; Smylie, Michael; Walker, John; Morris, Don; Cheng, Tina
Abstract: Introduction: Objective response rates (ORR) appear to be higher in melanoma patients who develop immune‐related adverse events (irAEs), but whether there is a similar association between irAEs and survival remains unknown. Materials and Methods: Patients with advanced melanoma treated with single‐agent pembrolizumab or nivolumab in the province of Alberta from June 2014 to May 2017 were identified through the provincial pharmacy database. Chart review identified and categorized all irAEs that occurred while on anti–programmed cell death protein 1 (PD‐1) checkpoint inhibitors. The primary objective was to compare overall survival (OS) with patients who developed any irAEs versus those who did not. Secondary outcomes included progression‐free survival (PFS) and ORR. Results: Among 186 patients, any‐grade and grade ≥3 irAEs occurred in 88 (47%) and 27 (15%) patients, respectively; one patient died of pneumonitis. In a landmark analysis excluding patients who died within the first 12 weeks, the median follow‐up was 24 months, 20 months in patients without any irAEs and 26 months in patients with irAEs ( p = .006). Median OS was 39 versus 23 months (hazard ratio [HR], 0.46; p = .001) for any irAE and no irAE, respectively, and median OS not reached versus 29 months for grade ≥3 irAEs and no grade ≥3 irAEs, respectively. In multivariate analysis, elevated lactate dehydrogenase correlated with reduced OS (HR, 2.34; p = .001), whereas each additional cycle of treatment received (HR, 0.94; p < .001) and development of grade ≥3 irAEs (HR, 0.29, p = .024) were significantly associated with longer OS. Conclusion: Anti‐PD‐1–associated grade ≥3 irAEs in patients with advanced melanoma is associated with better patient outcomes, including overall survival. Implications for Practice: Previous prospective randomized clinical trials demonstrate improved response rates in patients with melanoma who develop select adverse events. The current population‐based real‐world study in advanced melanoma reports an association with anti–programmed cell death protein 1 (PD‐1)–induced grade ≥3 immune‐related adverse events (irAEs) and better patient outcomes, including overall survival. These results suggest that irAEs may be a manifestation of a patient's ability to mount a systemic immune response from PD‐1–directed therapies, which may be associated with therapeutic benefit. The finding of irAEs coinciding with clinical benefit from these therapies supposes that these events are, by and large, unavoidable, and the critical management of irAEs remains essential for optimizing patient outcomes. Abstract : Real world patient data on efficacy, side‐effects, and clinical predictors of outcomes are lacking for immune checkpoint inhibitors. This multicenter population‐based study investigated the incidence of immune‐related adverse events and how the adverse events related to patient outcomes.